Re-assessment of silicon isotope reference materials using high-resolution multi-collector ICP-MS - Reynolds, B; Georg, R; Georg, R; Oberli, F; Oberli, F; Wiechert, U; Wiechert, U; Halliday, A; Halliday, A (2006)
Silicon isotope ratios can now be measured to very high precision using high-resolution multi-collector ICP-MS. Based on this technique we report that the Si isotope composition of IRMM-018 is significantly lighter than the NBS28 standard, in direct contrast to previously published results. Our data are also inconsistent with recently published absolute Si isotope abundances for these standards by Valkiers et al. (2005) and Ding et al. (2005). Instead, our results are coherent with the certified values for NIST standard SRM990 that was used to determine the atomic weight of Si, with a 30Si/29Si ratio that is over 6 permil lower for the same atomic weight. In order to avoid problems with future assessments of stable Si isotope variations, the NBS28 silica sand standard (RM8546) should remain the zero point. Therefore, an inter-laboratory calibration of NBS28 and other references materials is recommended to solve the observed discrepancies and establish a reliable scale for reporting Si isotopes. © the Royal Society of Chemistry 2006.